2021
DOI: 10.9734/jamb/2021/v21i1030393
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Aflatoxins in Rice Intended for Infant Flour Production in Ouagadougou, Burkina Faso

Abstract: A total of four samples of rice intended for infant flour production in Ouagadougou were received at the Physico-chemistry laboratory of Food Technology Department (DTA) for quality control. The latter were also tested for Aspergillus section Flavi presence and analyzed for aflatoxins B1, B2, G1 and G2 content using high performance liquid chromatography (HPLC). Among the twenty (20) strains of mold isolated from these samples, three Aspergillus section Flavi were obtained and cultivated in “Aspergillus flavus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
1
0
2
Order By: Relevance
“…These taxonomic descriptive features were used as the initial criteria for fungal identification. Similar features have been reported in previous studies by Ekwomadu et al, 2018 , Adelusi et al, 2022 , Khan et al, 2020 , Thathana et al, 2017 and Compaoré et al (2021) . However, it was acknowledged that the isolation and morphological identification were insufficient to fully establish the fungal isolate's identity at species level.…”
Section: Resultssupporting
confidence: 91%
“…These taxonomic descriptive features were used as the initial criteria for fungal identification. Similar features have been reported in previous studies by Ekwomadu et al, 2018 , Adelusi et al, 2022 , Khan et al, 2020 , Thathana et al, 2017 and Compaoré et al (2021) . However, it was acknowledged that the isolation and morphological identification were insufficient to fully establish the fungal isolate's identity at species level.…”
Section: Resultssupporting
confidence: 91%
“…Ce résultat corrobore avec celui de Compaoré et al (2021b) qui a obtenu 23 isolats de A flavus dans un cortège de champignons isolés sur des grains de maïs au Burkina Faso. A. flavus est particulièrement dangereux sur les semences car il produit plusieurs types d'aflatoxines à des taux pouvant atteindre 70,73µg/kg (Compaoré et al, 2021b).…”
Section: Au Niveau De La Variété Wariunclassified
“…Cependant, en raison de certaines conditions météorologiques de production, du mauvais séchage des épis couplé à des conditions inappropriées de stockage, les grains de maïs produits se retrouvent contaminés par des espèces de moisissures en provenance de l'air ou du sol (Ishrat & Shahnaz, 2009; Compaoré et al, 2021b). Ces espèces de champignons entrainent non seulement des fontes de semis et des retards de croissance à l'origine de baisse de rendements mais aussi sécrètent des métabolites secondaires comme les aflatoxines qui sont hautement toxiques pour l'homme et les animaux d'élevage (Bonzi et al, 2012 ;Compaoré et al, 2021b). De plus, environ 40% de la production du maïs est contaminé par les aflatoxines dans les pays en développement (Bamba, 2021).…”
Section: Introductionunclassified
“…Research on animals has demonstrated that H. pylori strains that are CagA-positive are the only ones that can cause stomach cancer. It has been noted that stomach cancer and peptic ulcers are more common in people with CagA positive H. pylori infections than in people with CagA negative infections [9]. In Libya, there are no available local data on the epidemiology of Helicobacter pylori infection from the southern regions of Libya, so the primary objective was to evaluate the incidence of seropositivity with H. pylori infection among patients with digestive disorders in the Wadi Al-Shati area.…”
Section: Introductionmentioning
confidence: 99%